2022
DOI: 10.3390/nu14132577
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Macronutrient Intake and Symptoms in Uninvestigated Dyspepsia: Evidence from a Population-Based, Cross-Sectional Study

Abstract: (1) Background: Limited evidence from laboratory-based studies suggests that specific dietary macronutrients, particularly fat, can induce dyspeptic symptoms. Through a population-based study, we investigated the relationship between dietary macronutrients and dyspeptic symptoms and sought to determine macronutrient intake thresholds to predict or prevent dyspepsia and reduce symptoms in patients with dyspepsia. (2) Methods: A total of 4763 Iranian people were enrolled in this population-based, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a recent large-scale cross-sectional study reported that patients with dyspepsia had higher dietary fat and lower carbohydrate intake than healthy controls. 29 Our heatmap analysis showed similar results, supporting previous evidence. PUFA, vitamin B 2 , protein, and carbohydrates are primarily abundant in fish such as salmon and tuna, whole grains like rice and wheat, and green vegetables.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a recent large-scale cross-sectional study reported that patients with dyspepsia had higher dietary fat and lower carbohydrate intake than healthy controls. 29 Our heatmap analysis showed similar results, supporting previous evidence. PUFA, vitamin B 2 , protein, and carbohydrates are primarily abundant in fish such as salmon and tuna, whole grains like rice and wheat, and green vegetables.…”
Section: Discussionsupporting
confidence: 90%
“…All authors did not find any significant differences in fat intake between the SIBO group and the control group [22,58,59]. A study conducted in Iran on patients with uninvestigated dyspepsia demonstrated a higher intake of fats compare to the control group (38.3% vs. 37.4%) [68].…”
Section: Fatmentioning
confidence: 89%
“…Agah and colleagues conducted a cross-sectional study involving Iranian adults to investigate the relationship between dietary macronutrients and dyspeptic symptoms [21]. They found that a higher fat or protein intake and lower carbohydrate intake were associated with a higher likelihood of experiencing uninvestigated dyspepsia [21].…”
mentioning
confidence: 99%